О возможности использования катковых гасителей в расширенном диапазоне частот - Легеза, В.П. (Проблемы управления и информатики, 2012)
Визначено умови використання коткових гасників для віброзахисту об’єктів у розширеному діапазоні частот. Встановлено, що ці умови пов’язані з величиною коефіцієнта сухого тертя між котком і сферичною поверхнею робочого тіла гасника та не накладають обмежень на величину частоти власних коливань несучого тіла. The conditions for usage of roller dampers for vibration protection of objects in the extended frequency range have been stated. It has been established that these conditions are related to the coefficient of dry friction between the roller and the spherical surface of the working body of the damper and do not impose restrictions on the value of frequency of natural oscillations of the carrier body.